The adoption of Internet by organizations in Singapore. - Lau, Kok Chiang. (2009)
Survey questionnaires were mailed, in March 1996, to 283 local organizations that were found to have published World Wide Web pages on the Internet. Over a six week period, 96 returns (33.6%) were received. The study examines various characteristics of these active and early organizational adopters of Internet. Drawing primarily on Rogers' theory of innovation, we will also be determining the factors that affected these organizations' timing of Internet adoption.